Impactos dos plásticos na praia de Itararé em São Vicente-SP - FERREIRA, Isabelly Gomes; FLOR, Júlia Roberta Gonçalves; VIEIRA, Marco Antônio de Souza Alves; SILVA, Victor Gabriel dos Santos (181, 2025)
A Praia de Itararé, localizada em São Vicente, no Litoral Sul de São Paulo, sendo de grande importância para a comunidade local e o turismo, porém apresenta problemas relacionados à poluição por resíduos plásticos. A metodologia utilizada foi de caráter qualiquantitativo, com coletas de resíduos, visando compreender a quantidade e o tipo de lixo presente. Os resultados evidenciam a persistência da poluição plástica, que ameaça o ecossistema local e a vida marinha.

This study aims to analyze the environmental impacts caused by improper plastic waste disposal on Itararé Beach, located in São Vicente on the southern coast of São Paulo. The approximately 2.9 km long beach is an important area for the local community and tourism but faces pollution issues related to plastic debris, especially during peak seasons. The research investigates the types and sources of plastic waste found on the beach and examines how material degradation affects water quality, marine life, and human health. It also discusses current legislation and highlights the importance of environmental education in promoting sustainable practices. The methodology combined quantitative and qualitative approaches, including waste collection from different sections of the beach to assess the quantity and variety of litter. The findings reveal persistent plastic pollution that threatens the local ecosystem and marine fauna, emphasizing the need for ongoing awareness campaigns and improved waste management policies. The study concludes that, despite existing efforts, cultural, economic, and enforcement challenges continue to contribute to the problem, underscoring the urgency of an integrated approach to preserving beaches and oceans.
Impacts of plastics on Itararé beach in São Vicente-SP
Keywords: Praias; Ecologia marinha; Prevenção e controle de poluição da água; Poluição do mar; Ambiente e Saúde